The Influence of Leadership Style towards Employee Performance at the Office of Cooperatives and MSMEs in Palopo City - Muhammad Aqsa; M. Risal; Husniawati Husniawati (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
Discipline is one of the benchmarks in seeing the performance of an employee. This study is focused on knowing, analyzing and describing the influence of leadership style variables on work discipline at the Office of Cooperatives and MSMEs in Palopo City. By using the saturated sampling technique, the sample used in this study was 76 respondents. In this study, questionnaires were distributed as a method to obtain data. From the output of SPSS processing, the research shows that the leadership style has a positive and significant impact on the work discipline of the Palopo City Cooperatives and UMKM Office employees.